IMPLEMENTASI BUDAYA RISET SEBAGAI MEDIA PENGEMBANGAN POTENSI PUSTAKAWAN PADA TAMAN BACAAN MASYARAKAT WADAS KELIR PURWOKERTO - Mukhamad Hamid Samiaji; Khomsiyatun, Umi (Perpustakaan Nasional RI, 2024)
Community Reading Gardens (TBM) is a form of lifelong learning facility that is expected to be able to increase people's interest in reading and literacy. More broadly, TBM provides access to information and educational resources that can stimulate the public to conduct research. The purpose of this study is to analyze the implementation of research culture as an effort to develop the potential of librarians in the Wadas Kelir Purwokerto Community Reading Park. The results of this study are: 1) the research culture for librarians was formed with the hope that librarians can follow the TBM curriculum development activities through the publication of scientific papers, the hope that librarians can live independently, and the hope that librarians can maintain the tradition of reading and writing; 2) the implementation of research culture is prioritized for the internal librarians of TBM Wadas Kelir and the general public by organizing various journal writing trainings, reference management training, and writing practices